Simultaneous determination of three active components in rat plasma by UPLC–MS/MS: Application to pharmacokinetic study after oral administration of Herba Sarcandrae extract. (2nd October 2016) - Zhang, Bin; Chen, Jianguo; Jiang, Qichuan; Wang, Xuefeng; Lu, Yan; Gong, Liang; Chen, Dong
Abstract: A rapid, specific and sensitive ultra‐performance liquid chromatography tandem mass spectrometry (UPLC‐MS/MS) method was developed and validated for determination of isofraxidin, rosmarinic acid and kaempferol‐3 ‐O ‐glucuronide in rat plasma using warfarin as an internal standard (IS). Separation was conducted on a Thermo Hypersil GOLD C18 column with linear gradient elution using methanol and water. Mass spectrometric detection was conducted using selected reaction monitoring (SRM) via an electrospray ionization (ESI) source. All analytes exhibited good linearity within their concentration ranges ( r > 0.9990). The lower limits of quantitations of isofraxidin, rosmarinic acid, and kaempferol‐3 ‐O‐ glucuronide were 1.31, 0.67 and 0.92 ng/mL, respectively. Intra‐ and inter‐day precisions of these investigated components exhibited an RSD within 11.7%, and the accuracy ranged from −12.5 to 15.0% at all QC levels. The developed method was successfully applied to a pharmacokinetic study of isofraxidin, rosmarinic acid, and kaempferol‐3 ‐O‐ glucuronide in rats after oral administration of Herba Sarcandrae Extract.